Assessing the inflammation in pediatric MOGAD: Significance of CSF HMGB1 and related biomarkers - Wang, Xin; Zhao, Ruibin; Fan, Jiayu; Liu, Chong; Zhang, Li; Yang, Huafang; Wang, Weiyi (Frontiers in Immunology, 2025)
Background and purposeMyelin-oligodendrocyte glycoprotein antibody associated disease (MOGAD) is a common inflammatory disease of the central nervous system (CNS) in children that can lead to demyelination. Evaluation and monitoring of biomarkers associated with its pathogenesis would provide vital information on disease progression and therapeutic assessment.MethodsWe assessed NLRP3, HMGB1, IL-6, and IL-33 levels in the cerebrospinal fluid (CSF) of pediatric patients with MOGAD at different time points and their association with the risk of disease. We recruited 30 patients with MOGAD (20 in the acute phase and 10 in remission) and 10 control patients with noninflammatory demyelinating disease. The expanded disability status scale (EDSS) was used to assess disease severity.ResultsNLRP3, HMGB1, and IL-6 levels in the CSF were significantly higher in patients with MOGAD during the acute phase than in remission (P < 0.05, P < 0.05, P < 0.05) and the control group (P < 0.01, P < 0.0001, P < 0.01). HMGB1 levels were significantly correlated with NLRP3 levels (P < 0.01) during the acute phase. Moreover, we found notable correlation between HMGB1 levels and EDSS (P < 0.05) scores. IL-6 levels were significantly correlated with the total number of attacks (P < 0.05), but not with EDSS scores.ConclusionsThese findings suggest that NLRP3, HMGB1, and IL-6 in the CSF may be potential therapeutic targets and are at least partly involved in the pathogenesis of pediatric MOGAD. HMGB1 in the CSF may be a potential biomarker correlating with pediatric MOGAD severity. Further investigations are warranted to validate potential cytokine pathways between that NLRP3, HMGB1, and IL-6 of MOGAD.